World Economic and Financial Surveys, Primary Commoditie, 1989 : Primary Commodities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper provides an analysis of the market developments in 1988 with respect to primary commodities and the outlook for these commodities in the near and medium term. Attention is focused on the major nonfuel primary commodities traded in international markets. Movements in the overall price index and in price indices for the major groups of commodities have been mirrored by an inverse movement in stocks of commodities. Beginning-of-year stocks of all nonfuel commodities-measured in terms of months of consumption-increased during the first half of the 1980s and peaked in 1986. Movements in primary commodity prices convey important information in several ways: they signal changes in the major source of export earnings for most developing countries; they indicate changes in a significant component of the cost of producing many manufactured goods; and they may be a helpful leading indicator of changes in inflation in industrial countries. The negotiating groups established for the Uruguay Round met on a number of occasions throughout the year to discuss a wide range of issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet